Trend Manajemen Kurikulum Adaptif di Era Digital Implementasi Personalized Learning dalam Sekolah Swasta - rosyidatul umah, luluk; Khaudli, M. Imam (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2025)
This research aims to analyze the trends in adaptive curriculum management based on personalized learning in the context of digitization in private schools, as well as to identify the supporting and hindering factors for its implementation. Conducted at SMA Darussalam Blokagung, the research employs a qualitative approach with a case study to gain an in-depth understanding of the application of adaptive curriculum management that integrates Islamic educational values and technological innovations. Data were collected through non-participatory observation, in-depth interviews with the principal, vice principal, teachers, and students, as well as documentation of the curriculum and digital learning materials. Data analysis was conducted in stages through data reduction, thematic presentation, and consistency verification using content, discourse, and interpretative analysis methods. The research results indicate that curriculum adaptation has produced a multi-platform hybrid learning model that combines face-to-face and online learning, enhancing student flexibility and engagement. The implementation of personalized learning has been proven to effectively improve academic achievement and adaptive culture with the use of digital platforms that support learning according to individual needs. Digital curriculum management based on a Learning Management System creates a flexible and real-time responsive learning ecosystem, allowing for rapid adjustments to student needs and supporting active stakeholder engagement. Overall, this study confirms that digital integration in curriculum management can build an adaptive, inclusive, and collaborative learning environment relevant to modern educational challenges. Keywords: Adaptive Curriculum; Personalized Learning; Digital Learning.